N-acetylcysteine effects on sinonasal cilia function - Kapusuz Gencer, Zeliha; Saydam, Levent; A. Cohen, Noam; Cingi, Cemal (ENT Updates, 2015)
Objective: To evaluate the pharmacological effects of the N-acetylcysteine (NAC) on human respiratory epithelial cultures specifically addressing electrolyte transport and cilia beat frequency. Methods: Well-differentiated human bronchial epithelial cultures grown at an air liquid interface were treated on the apical or basolateral surface with varying concentrations of NAC. The best NAC concentration for ideal cilia beat frequency was found. The effects of NAC were evaluated on cilia beat frequency. After the effect of N-acetylcysteine on beat rate was found, its efficiency was investigated by ATP or IBMX to understand its mechanism of action. Changes in ciliary beat frequency were determined using the Sissons-Ammons video analysis system. Results: Maximal stimulatory effect on cilia function was evident at 10 mg/ml NAC concentration. After wash up, cilia movement were increased very dramatically. This increase of cilia beat frequency was even higher after NAC plus IBMX and NAC plus ATP washings. Conclusion: Apical application of NAC prominently stimulates cilia beat frequency and after wash up, cilia movement was increased very dramatically. After NAC use by washing with PBS in clinical efficacy can be enhanced.